Single-cell RNA sequencing for the study of lupus nephritis. Issue 1 (4th June 2019) - Der, Evan; Suryawanshi, Hemant; Buyon, Jill; Tuschl, Thomas; Putterman, Chaim
Abstract : Single-cell RNA sequencing (scRNA-seq) has recently undergone rapid advances in the development of this technology, leading to high throughput and accelerating discovery in many biological systems and diseases. The single-cell resolution of the technique allows for the investigation of heterogeneity in cell populations, and the pinpointing of pathological populations contributing to disease. Here we review the development of scRNA-seq technology and the analysis that has evolved with the ever-increasing throughput. Finally, we highlight recent applications of scRNA-seq to understand the molecular pathogenesis of lupus and lupus nephritis.